2006
DOI: 10.1212/01.wnl.0000240057.71766.71
|View full text |Cite
|
Sign up to set email alerts
|

Prior TIA, lipid-lowering drug use, and physical activity decrease ischemic stroke severity

Abstract: Both regular physical activity and lipid-lowering drugs should be prospectively evaluated to determine whether they reduce the severity of ischemic stroke.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
122
0
5

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(134 citation statements)
references
References 44 publications
7
122
0
5
Order By: Relevance
“…Multiple groups have evaluated the association between statin pretreatment and the severity of stroke. 7,34,35 Similar to ours, findings in most studies do not suggest a beneficial role for statins in reducing the severity of clinical symptoms at presentation. 7,35 Previous observations have shown a trend toward better functional outcomes [34][35][36] and a reduction in ischemic progression/ recurrent events 7 or in-hospital mortality in patients pretreated with statins.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Multiple groups have evaluated the association between statin pretreatment and the severity of stroke. 7,34,35 Similar to ours, findings in most studies do not suggest a beneficial role for statins in reducing the severity of clinical symptoms at presentation. 7,35 Previous observations have shown a trend toward better functional outcomes [34][35][36] and a reduction in ischemic progression/ recurrent events 7 or in-hospital mortality in patients pretreated with statins.…”
Section: Discussionsupporting
confidence: 84%
“…7,34,35 Similar to ours, findings in most studies do not suggest a beneficial role for statins in reducing the severity of clinical symptoms at presentation. 7,35 Previous observations have shown a trend toward better functional outcomes [34][35][36] and a reduction in ischemic progression/ recurrent events 7 or in-hospital mortality in patients pretreated with statins. 7 Furthermore, a recent meta-analysis of observational and randomized studies looking only at patients receiving statins at the time of ischemic stroke versus those who were not, showed an improvement in the functional independence rate and survival in the statin-treated subgroup.…”
Section: Discussionsupporting
confidence: 84%
“…Multiple studies using human and animal models have shown that preischemic physical activity reduces stroke impact on functional motor outcomes, edema, and infarct volume. The same studies also attributed these benefits to the mechanism of decreasing inflammation, and increasing brain-derived neurotrophic factor (BDNF) expression [2][3][4][5][6]. In many cases, however, stroke patients are unable to adhere to the physical activity regimen following their ischemic episodes due to a wide range of individual factors such as stroke severity, preexisting and comorbid conditions, motivation, fatigue, and depression.…”
Section: Introductionmentioning
confidence: 99%
“…Des résultats expérimentaux complémen-taires ont démontré que l'effet de ces différentes classes, en particulier celle des statines, ne persistait pas au-delà de quelques jours après l'arrêt de l'administration de la molécule, avant la réalisation de l'ischémie, suggérant que l'effet neuroprotecteur préventif n'est pas lié à un mécanisme de préconditionnement mais plus à la présence du médicament dans l'organisme au moment de la survenue de l'accident ischémique cérébral. Il n'en demeure pas moins que, quel que soit le mécanisme en jeu, la neuroprotection préventive reste cliniquement pertinente puisque plusieurs études cliniques ont permis de montrer que les patients traités par des agents hypolipémiants ou pratiquant un exercice physique régulier avant la survenue d'un accident ischémique cérébral ont une sévérité moindre des symptômes cliniques [14].…”
Section: Les Stratégies De Neuroprotectionunclassified